2008
DOI: 10.1007/s00787-008-0704-x
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing behaviors in preadolescents: familial risk to externalizing behaviors, prenatal and perinatal risks, and their interactions

Abstract: Background: Accumulating evidence indicates that there is a rich and varied interplay between persons and their environments, which strongly suggests that this involves gene-environment correlations and interactions. We investigated whether familial risk (FR) to externalizing behaviors and prenatal and perinatal risk factors, separately or in interaction with each other, predicted externalizing behaviors. Methods: The subjects were 10- to 12-year-old preadolescents who were taking part in TRAILS, a large prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
59
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 49 publications
4
59
2
Order By: Relevance
“…Indeed, it appears that there may be complex relations between prenatal smoking exposure and the phenotypes of interest in the current investigation. Little and Sing (1987) found that the pattern of genetic and environmental influences on infant birth weight differed for smoking and nonsmoking mothers, and other investigations have reported associations between prenatal cigarette smoke exposure, low birth weight, and behavioral problems in children (Buschgens et al, 2009; Kramer, 1987; Langley et al, 2007), though these associations may be confounded by factors such as maternal ADHD symptoms (Thapar, et al, 2009). Because smoking during pregnancy was reported by very few mothers in the current investigation, we were unable to examine whether prenatal cigarette exposure moderated or accounted for the associations between birth weight and disruptive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it appears that there may be complex relations between prenatal smoking exposure and the phenotypes of interest in the current investigation. Little and Sing (1987) found that the pattern of genetic and environmental influences on infant birth weight differed for smoking and nonsmoking mothers, and other investigations have reported associations between prenatal cigarette smoke exposure, low birth weight, and behavioral problems in children (Buschgens et al, 2009; Kramer, 1987; Langley et al, 2007), though these associations may be confounded by factors such as maternal ADHD symptoms (Thapar, et al, 2009). Because smoking during pregnancy was reported by very few mothers in the current investigation, we were unable to examine whether prenatal cigarette exposure moderated or accounted for the associations between birth weight and disruptive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent cohort of preadolescents from the general population, interactions between a family history of externalizing behavior and maternal prenatal smoking have been reported. 19 In the etiology of ADHD as such, evidence regarding a role of gene-environment (mainly prenatal smoking exposure) interactions has been increasing 16 : for example, children who had been exposed to prenatal smoking demonstrated more severe hyperactive-impulsive symptoms if they had 10-repeat allele of the dopamine transporter 1. 20 The effects of pregnancy and delivery complications and smoking exposure in utero may be understood through fetal hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking during pregnancy is harmful for mother and child, with increased risk of prenatal complications such as risk of abruption, placenta previa, perinatal mortality, impaired fetal growth, higher neonatal stress and irritability, hearing loss, and respiratory problems (Andres and Day, 2000;Cornelius and Day, 2000;Cornelius et al, 2004;Fried, 1998;Mccartney et al, 1994;Stroud et al, 2009). Cigarette exposure also has long-lasting effects on developmental outcomes such as externalizing behavior problems (Buschgens et al, 2009;Porath and Fried, 2005;Silberg et al, 2003;Wakschlag et al, 2011) and carries with it a higher risk of smoking in later childhood and adolescence (Cornelius et al, 2004;O'Callaghan et al, 2006).…”
mentioning
confidence: 99%